The straight line joining the points A(3,-5) and B(6,k) has a gradient of 4.
Gradient is the slope
So the slope of the line joining the points A(3,-5) and B(6,k) is 4
Slope of line joining two points = ![\frac{y_2-y_1}{x_2-x_1}](https://tex.z-dn.net/?f=%5Cfrac%7By_2-y_1%7D%7Bx_2-x_1%7D)
A(3,-5) and B(6,k) are (x1,y1) and (x2,y2)
slope = ![\frac{y_2-y_1}{x_2-x_1}](https://tex.z-dn.net/?f=%5Cfrac%7By_2-y_1%7D%7Bx_2-x_1%7D)
slope = ![\frac{k-(-5)}{6-3}=\frac{k+5)}{3}](https://tex.z-dn.net/?f=%5Cfrac%7Bk-%28-5%29%7D%7B6-3%7D%3D%5Cfrac%7Bk%2B5%29%7D%7B3%7D)
We know slope =4
![\frac{k+5)}{3}=4](https://tex.z-dn.net/?f=%5Cfrac%7Bk%2B5%29%7D%7B3%7D%3D4)
Cross multiply and solve for k
k + 5 = 12
k = 7
The value of k = 7
In the division rule you subtract the exponents<span> when </span>dividing<span> numbers with the same base. </span>One<span> rule for exponents is that exponents add when you have the same base. This works for any number x that you want to plug in except for x = </span>0<span>,because </span>0/0<span> is indeterminate (it is like dividing </span>zero<span> by </span>zero<span>). No matter what number we use when it is raised to the </span>zero power<span> it will always be </span>1.
Answer:
![-x^{2}+4x](https://tex.z-dn.net/?f=-x%5E%7B2%7D%2B4x)
Step-by-step explanation:
we have
![(x^{2}+x)-(2x^{2} -3x)](https://tex.z-dn.net/?f=%28x%5E%7B2%7D%2Bx%29-%282x%5E%7B2%7D%20-3x%29)
step 1
Eliminate the parenthesis
![x^{2}+x-2x^{2} +3x](https://tex.z-dn.net/?f=x%5E%7B2%7D%2Bx-2x%5E%7B2%7D%20%2B3x)
The symbol of the term 3x is incorrect, must be positive instead of negative
so
![-(-3x)=+3x](https://tex.z-dn.net/?f=-%28-3x%29%3D%2B3x)
Group terms that contain the same variable
![(x^{2}-2x^{2})+(x+3x)](https://tex.z-dn.net/?f=%28x%5E%7B2%7D-2x%5E%7B2%7D%29%2B%28x%2B3x%29)
Combine like terms
![-x^{2}+4x](https://tex.z-dn.net/?f=-x%5E%7B2%7D%2B4x)
Answer:
Step-by-step explanation:
1,8
5,7
2,3
Answer:
She swam a total distance of 2 1/4 miles in those three days.
Step-by-step explanation:
Okay, so- The first thing you need to do is make all denominators equal to make these fractions able to be added together. So, I made all denominators 12. (Tell me if you don't know how to make them all the same denominator, and I'll be happy to help!)
<u>2/3 = 8/12 </u>
<u>3/4 = 9/12 </u>
<u>5/6 = 10/12</u>
Then, I added the numerators together. Like this:
<u>8 + 9 + 10 = 27 </u>
So, this would be:
<u>27/12</u>
Lastly, I changed this improper fraction to a mixed number. I multiplied the denominator twice because it looked like it would be closest to 27 without going over.
<u>12 * 2 = 24 </u>
<em>The "2" will be the whole number in the mixed fraction.</em> Now, I'm going to subtract 24 from the numerator.
<u>27 - 24 = 3 </u>
<u>2 3/12</u>
After simplified, the fraction will be:
2 1/4
<h3>Hope this helps! Let me know if you need help with something else or if you have questions about this problem !</h3>